ENHANCING LANGUAGE AWARENESS IN MULTILINGUAL EFL CLASSES - Tri Rina Budiwati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2010)
The fact that any language has its set of varieties serves to emphasisethat it is important to have the right attitude and possess sufficientknowledge of the language to function in a multilingual society.Living in such a society, Indonesians must realize that an awarenessneeds to be created amongst EFL learners in the country aboutpossessing the right attitude and knowledge of English, and this canonly be done through the education system. This paper explores theconcept of language awareness and links this specifically to methods ofdeveloping EFL awareness among multilingual students at theAhmad Dahlan University in Yogyakarta, Indonesia. The study isgrounded in Hawkins’ and Fairclough’s concepts of Critical LanguageAwareness, and its development and application by other experts.These basic concepts are employed to understand the significance oflanguage awareness and the implications on EFL teachingmethodology. The study reveals that Language Awarenessundoubtedly has great significance for both EFL teachers andstudents. This paper proposes some ways to enhance students’language awareness that could be applied in multilingual EFL classes.